186k views
5 votes
A=(2 3)
(-1 4)

Calculate A^2-6A+11I

1 Answer

1 vote

Answer:

A² - 6A + 11 I =
\left[\begin{array}{ccc}0&0\\0&0\end{array}\right]

Explanation:

Given the matrix


A=\left[\begin{array}{ccc}2&3\\-1&4\end{array}\right]

Calculate A² - 6A + 11 I


A^2 = A*A= \left[\begin{array}{ccc}2&3\\-1&4\end{array}\right] *\left[\begin{array}{ccc}2&3\\-1&4\end{array}\right] = \left[\begin{array}{ccc}2*2-3*1&2*3+3*4\\-1*2-4*1&-1*3+4*4\end{array}\right] =\left[\begin{array}{ccc}1&18\\-6&13\end{array}\right]


6A=6*\left[\begin{array}{ccc}2&3\\-1&4\end{array}\right] =\left[\begin{array}{ccc}12&18\\-6&24\end{array}\right]


11 I = 11 * \left[\begin{array}{ccc}1&0\\0&1\end{array}\right] =\left[\begin{array}{ccc}11&0\\0&11\end{array}\right]

∴ A² - 6A + 11 I =
\left[\begin{array}{ccc}1&18\\-6&13\end{array}\right] -\left[\begin{array}{ccc}12&18\\-6&24\end{array}\right] +\left[\begin{array}{ccc}11&0\\0&11\end{array}\right] =\left[\begin{array}{ccc}0&0\\0&0\end{array}\right]

User CoolEsh
by
5.7k points